2020
DOI: 10.1186/s40834-020-00133-6
|View full text |Cite
|
Sign up to set email alerts
|

Why does uptake of family planning services remain sub-optimal among Nigerian women? A systematic review of challenges and implications for policy

Abstract: Background Over the years, family planning uptake in Nigeria has remained low and this is as a result of the various challenges and barriers faced by women. The aim of this study was to systematically review studies on family planning services undertaken in Nigeria in order to understand the challenges to uptake of the services and the policy implications. Methods A PubMed search was performed in June 2020 and studies that investigated challenges of family planning uptake in Nigeria published in English betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 27 publications
4
35
0
1
Order By: Relevance
“…Those with tertiary education have lower unmet need for family planning than others. This finding corroborates previous research that lower unmet need for contraceptive use is recorded among women with more than secondary education [ 7 , 40 , 41 ], and further indicates that the need for higher education is key to attending met need for family planning. This is because it equally inspires the right decision making towards contraceptive especially in developing countries where access to modern contraceptives is generally low [ 15 , 17 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Those with tertiary education have lower unmet need for family planning than others. This finding corroborates previous research that lower unmet need for contraceptive use is recorded among women with more than secondary education [ 7 , 40 , 41 ], and further indicates that the need for higher education is key to attending met need for family planning. This is because it equally inspires the right decision making towards contraceptive especially in developing countries where access to modern contraceptives is generally low [ 15 , 17 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Those with 1-4 children have higher unmet need for family planning than those without children. Previous studies reported that women with two or more children have higher contraceptive use than those with only one child [ 36 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The government of Nigeria and development partners in the country are making efforts to address supply-side issues related to contraceptive use and ensure that it becomes more widely acceptable both for spacing and limiting the number of children among women of childbearing age. Studies have shown however that demand-side challenges for family planning persist across the country and may be more difficult to tackle ( 27 – 32 ). This article is an attempt to contribute to the body of knowledge in identifying some household characteristics that may contribute to the demand-side challenges for family planning acceptance and use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies with girls in Ghana have shown no association [ 22 , 26 ], whilst a study in Tanzania showed higher contraceptive uptake associated with increased knowledge [ 12 ]. However, there is extensive evidence from Nigeria that misconceptions about contraception have a negative effect on contraceptive uptake [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%